Aseptic Pharmaceutical Manufacturing : technology for the 1990s. (United States of America : Interpharm Press, 1987)
The first two pharmaceutical technology conference symposia on aseptic pharmaceutical processing (1984 and 1985) were chaired by the editors. It became clear during those meetings that existing texts covering aseptic pharmaceutical manufacturing defined 'state-of-the-art" as that of decade earlier.